IMPACT OF THE USE OF SOCIAL NETWORKS ON THE DEVELOPMENT OF ANXIETY AND DEPRESSION DISORDERS IN YOUNG ADULTS - Moura Carias, Pedro; Almeida do Nascimento, Evelyn; Almeida Cabral dos Santos Lugão, Matheus; Pedro Rocha Morozini, João; Leite Bicalho, Rebeca; Garcia Lima, Carolina; Henrique Braga, Pedro; Fernanda Santos, Evelyn; Luiza Cerutti Dutra, Ana; Bandeira Lima, Júlia; Costa Pignaton, Maycon; Stein de Siqueira Varejão, Amanda; et al. (Health and Society, 2024)
Social networks have transformed the way young adults relate, consume information and construct their identities. Although these platforms provide opportunities for connection and learning, their excessive use has been associated with the development of anxiety and depression disorders. Prolonged exposure to unrealistic standards of life and beauty, social interaction mediated by screens and technological dependence are factors that can compromise the mental health of this population. The aim of this study is to analyze the impact of social media use on the development of anxiety and depression disorders in young adults, identifying risk factors and opportunities for preventive interventions. This study used a qualitative approach through a literature review, with the aim of analyzing the impact of social media use on mental health. The focus was on psychological effects, patterns of behavior and implications for quality of life, with an emphasis on young people and adolescents. Recent studies indicate that excessive use of social networks is related to feelings of inadequacy, social isolation and low self-esteem, factors that increase vulnerability to mental health disorders. Social comparison, fueled by algorithms that prioritize highly visually appealing content, and cyberbullying emerge as recurring triggers for anxiety and depression. In addition, the sleep disruption caused by using these platforms at night aggravates psychological symptoms. Strategies such as promoting the conscious use of social networks and developing emotional skills can reduce these negative impacts. Therefore, excessive and unregulated use of social media can significantly contribute to the increase in cases of anxiety and depression in young adults. It is essential to promote digital education, limit usage time and create awareness campaigns to mitigate the adverse effects of social media, protecting the mental health of this age group.